A solid electrolyte membrane and its preparation method and application

Through the combination of modified inorganic nanofiber membrane and active materials, the problem of narrow temperature range and insufficient mechanical properties of polymer solid electrolytes in lithium-ion batteries is solved, and higher mechanical strength and conductivity are achieved, and the safety and cycle stability of the battery are improved.

CN119069776BActive Publication Date: 2025-05-02ZHUJI PAWA NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411545258.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-05-02
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The polymer solid electrolytes in existing lithium-ion batteries have a narrow temperature range and insufficient mechanical properties, which makes it difficult for the battery to operate safely when the local temperature is too high.

Method used

The solid electrolyte membrane composed of modified inorganic nanofiber membrane and active materials is modified by GPTMS, PEI and PES to enhance the mechanical properties and conductivity of the electrolyte membrane, and the modified inorganic nanofiber membrane is coated with the active materials to build a three-dimensional ion transport channel.

Benefits of technology

It improves the mechanical strength and conductivity of the solid electrolyte membrane, enhances the transmission capacity of lithium ions, effectively prevents the penetration of lithium dendrites, and improves the safety and circulation stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069776B_ABST
    Figure CN119069776B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium-ion battery materials, and discloses a solid electrolyte membrane and a preparation method and application thereof, wherein the solid electrolyte membrane comprises a modified inorganic nanofiber membrane and an active material, wherein the active material is coated on at least part of the surface of the modified inorganic nanofiber membrane; the modified inorganic nanofiber membrane is prepared by modifying inorganic oxides with GPTMS (3-glycidyloxypropyltrimethoxysilane), PEI (polyethyleneimine) and PES (polyethersulfone). By modifying the inorganic oxides with GPTMS, PEI and PES, the transmission of lithium ions in the electrolyte membrane can be promoted, the mechanical properties of the solid electrolyte membrane can be enhanced, and the conductivity and safety performance of the solid electrolyte membrane can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery materials and relates to an electrolyte, in particular to a solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are widely used in electronic devices due to their high energy and power density. The electrolytes in lithium-ion batteries usually come in liquid, semi-solid and solid forms. Liquid electrolytes used in lithium batteries are prone to electrode corrosion, leakage, combustion, and even explosion, which can cause safety issues. Semi-solid and solid electrolytes are more stable than liquid electrolytes, reducing the possibility of electrode corrosion, leakage, combustion and explosion.

[0003] The initial main direction of solid electrolyte research was polymer solid electrolytes, mainly PEO series. Polymer solid electrolytes are highly safe, can be prepared into various shapes, and are compatible with existing battery manufacturing technology. However, polymer solid electrolytes have a narrow applicable temperature range and insufficient mechanical properties, which makes it difficult for the battery to work safely when the local temperature is too high. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a solid electrolyte membrane; in the second aspect, the present invention provides a method for preparing a solid electrolyte membrane; in the third aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a solid electrolyte membrane, comprising a modified inorganic nanofiber membrane and an active material, wherein the active material is coated on at least a portion of the surface of the modified inorganic nanofiber membrane; the modified inorganic nanofiber membrane is made of inorganic oxides modified by GPTMS (3-glycidyloxypropyltrimethoxysilane), PEI (polyethyleneimine) and PES (polyethersulfone).

[0006] Preferably, the inorganic oxide is any one or more of aluminum oxide, silicon oxide and magnesium oxide.

[0007] Preferably, the active material is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5C l0.5 Br 0.5 , Li 5.7 PS 4.7 C l1.3 Any one or two or more of the above.

[0008] In a second aspect, the present invention provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0009] Step 1, dispersing GPTMS and inorganic oxide in a first solvent, reacting in an oil bath, and performing solid-liquid separation to obtain solid particles;

[0010] Step 2, dispersing the solid particles and PEI in a second solvent, adjusting the pH value of the reaction system to 8-9, and performing solid-liquid separation after oil bath reaction to obtain precipitated particles;

[0011] Step 3, dispersing the precipitated particles and PES in a second solvent to obtain a spinning solution, drawing the spinning solution into filaments by electrospinning, and then preparing a modified inorganic nanofiber membrane;

[0012] Step 4, dispersing the active material and the polymer in a third solvent to obtain a slurry, dropping the slurry on the modified inorganic nanofiber membrane, and drying under an inert atmosphere to obtain the solid electrolyte membrane;

[0013] Preferably, the inorganic oxide is any one or two or more of aluminum oxide, silicon oxide and magnesium oxide.

[0014] Preferably, the active material is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5C l0.5 Br 0.5 , Li 5.7 PS 4.7 C l1.3 Any one or two or more of the above.

[0015] Preferably, in step 1, after GPTMS (3-glycidyloxypropyltrimethoxysilane) and the inorganic oxide are dispersed in the first solvent, the concentration of the inorganic oxide in the first solvent is 10-35 g / L; and the concentration of GPTMS in the first solvent is 0.13-0.27 mol / L.

[0016] Preferably, in step 1, the first solvent is any one or more of toluene, acetone and diethyl ether.

[0017] Preferably, in step 1, the oil bath temperature is 90-120° C., and the oil bath time is 10-15 h; more preferably, the oil bath of the mixture of GPTMS, inorganic oxide and toluene is accompanied by a stirring process.

[0018] Preferably, in step 1, the solid-liquid separation is centrifugal separation, the centrifugal speed is 6000-8000 r / min, and the centrifugation is 10-20 min.

[0019] Preferably, in step 1, after solid-liquid separation, the solid particles obtained are washed 2 to 4 times with methanol; more preferably, the washing method is centrifugal washing, the centrifugal speed is 6000 to 8000 r / min, and the centrifugation is 10 to 20 min.

[0020] Preferably, in step 2, after the solid particles and PEI (polyethyleneimine) are dispersed in the second solvent, the concentration of the solid particles in the second solvent is 10-30 g / L; the concentration of PEI in the second solvent is 10-30 g / L.

[0021] Preferably, in step 2, the second solvent is any one or both of DMF (N,N-dimethylformamide) and ethanol.

[0022] Preferably, in step 2, the oil bath temperature is 70-100° C., and the oil bath time is 15-30 h.

[0023] Preferably, in step 3, the concentration of precipitated particles in the spinning solution is 30-75 g / L; the concentration of PES in the spinning solution is 200-500 g / L.

[0024] Preferably, in step 4, the polymer is any one or more of polytetrafluoroethylene, nitrile rubber, polyethylene oxide, and silicone rubber.

[0025] Preferably, in step 4, the third solvent is any one or more of toluene, chloroform, anisole and xylene.

[0026] Preferably, in step 4, the concentration of the active substance in the slurry is 100-400 g / L; the concentration of the polymer in the slurry is 4-16 g / L.

[0027] Preferably, 0.12-0.2 g of slurry is dropped on each square centimeter of the inorganic nanofiber membrane.

[0028] In a third aspect, the present invention provides a battery comprising the above-mentioned solid electrolyte membrane or the solid electrolyte membrane prepared by the above-mentioned preparation method.

[0029] Compared with the prior art, the present invention has the following obvious beneficial effects:

[0030] By modifying inorganic oxides with GPTMS, PEI, and PES, firstly, ether radicals and sulfonyl radicals can be compounded in the solid electrolyte membrane. The ether radicals and sulfonyl radicals act as Lewis bases to bind and dissociate with lithium ions during the charge and discharge process, promoting the transmission of lithium ions in the electrolyte membrane; secondly, the continuous modification of inorganic oxides by GPTMS and PEI can improve the dispersibility of inorganic oxides in PES solution, thereby enhancing the mechanical properties of the solid electrolyte membrane; thirdly, inorganic oxides, as inert fillers, can reduce the crystallinity of PES, improve the ionic conductivity of PES, and thus improve the conductivity of the solid electrolyte membrane. The combination of inorganic nanofiber membranes and active materials to construct a three-dimensional ion transmission channel can effectively prevent safety accidents caused by the penetration of lithium dendrites during the charge and discharge process while improving the mechanical strength of the electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of the A-Al2O3-SPE inorganic nanofiber membrane prepared in step 3 of Example 1;

[0032] Figure 2 This is a SEM image of the A-SiO2-SPE inorganic nanofiber membrane prepared in step 3 of Example 2;

[0033] Figure 3 This is a SEM image of the A-MgO-SPE inorganic nanofiber membrane prepared in step 3 of Example 3;

[0034] Figure 4 The cycle performance test diagram of the battery assembled with the solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 4;

[0035] Figure 5 The time-voltage curve of a Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Example 1;

[0036] Figure 6 The time-voltage curve of a Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Comparative Example 1;

[0037] Figure 7 The time-voltage curve of the Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Comparative Example 2;

[0038] Figure 8 The time-voltage curve of the Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Comparative Example 3;

[0039] Fig. 9 The time-voltage curve of the Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Comparative Example 4. DETAILED DESCRIPTION

[0040] The present invention provides the following specific technical solutions.

[0041] In a first aspect, the present invention provides a solid electrolyte membrane, comprising a modified inorganic nanofiber membrane and an active material, wherein the active material is coated on at least a portion of the surface of the modified inorganic nanofiber membrane; the modified inorganic nanofiber membrane is made of inorganic oxides modified by GPTMS (3-glycidyloxypropyltrimethoxysilane), PEI (polyethyleneimine) and PES (polyethersulfone).

[0042] After research, the inventors obtained the scheme of modifying inorganic oxides with GPTMS, PEI and PES. On the one hand, PES has excellent heat resistance, physical and mechanical properties and electronic insulation properties, and the ether oxygen and sulfonyl groups in its structure can combine and dissociate with lithium ions as Lewis bases during the charge and discharge process, promoting the transmission of lithium ions in the electrolyte; on the other hand, the modification of inorganic oxides by GPTMS and PEI can improve the dispersibility of inorganic oxides in PES solution, thereby enhancing the mechanical properties of the solid electrolyte membrane; on the other hand, inorganic oxides, as inert fillers, can reduce the crystallinity of PES, improve the ionic conductivity of PES, and thus improve the conductivity of the solid electrolyte membrane; inorganic oxides are modified by GPTMS, PEI and PES, and the modified inorganic oxides are used as the skeleton of the solid electrolyte membrane, and then the active materials are compounded on the surface of the skeleton. The two are combined to construct a three-dimensional ion transmission channel, which can effectively prevent the safety accidents caused by the penetration of lithium dendrites during the charge and discharge process while improving the mechanical strength of the electrolyte membrane.

[0043] Preferably, the inorganic oxide is any one or more of aluminum oxide, silicon oxide and magnesium oxide.

[0044] Preferably, the active material is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5C l0.5 Br 0.5 , Li 5.7 PS 4.7 C l1.3 Any one or two or more of the above.

[0045] In a second aspect, the present invention provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0046] Step 1, dispersing GPTMS and inorganic oxide in a first solvent, reacting in an oil bath, and performing solid-liquid separation to obtain solid particles;

[0047] Step 2, dispersing the solid particles and PEI in a second solvent, adjusting the pH value of the reaction system to 8-9, and performing solid-liquid separation after oil bath reaction to obtain precipitated particles;

[0048] Step 3, dispersing the precipitated particles and PES in a second solvent to obtain a spinning solution, drawing the spinning solution into filaments by electrospinning, and then preparing a modified inorganic nanofiber membrane;

[0049] Step 4, dispersing the active material and the polymer in a third solvent to obtain a slurry, dropping the slurry on the modified inorganic nanofiber membrane, and drying under an inert atmosphere to obtain the solid electrolyte membrane;

[0050] Among them, the inorganic oxide is any one or more of aluminum oxide, silicon oxide, and magnesium oxide; the active material is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5C l0.5 Br 0.5 , Li 5.7 PS 4.7 C l1.3 Any one or two or more of the above.

[0051] Preferably, in step 1, after GPTMS (3-glycidyloxypropyltrimethoxysilane) and the inorganic oxide are dispersed in the first solvent, the concentration of the inorganic oxide in the first solvent is 10-35 g / L; and the concentration of GPTMS in the first solvent is 0.13-0.27 mol / L.

[0052] If there is too little GPTMS, the reaction between GPTMS and the hydroxyl groups on the surface of the inorganic oxide is not complete, resulting in some inorganic oxides not being complexed with the methoxy groups of GPEMS, affecting the modification effect. In practical applications, an excess of GPTMS can be used to ensure the modification effect.

[0053] Preferably, in step 1, the first solvent is any one or more of toluene, acetone and diethyl ether.

[0054] In actual application, the first solvent used is toluene, acetone, or ether with a purity greater than 99% on the market.

[0055] Preferably, in step 1, the oil bath temperature is 90-120° C., and the oil bath time is 10-15 h; more preferably, the oil bath of the mixture of GPTMS, inorganic oxide and toluene is accompanied by a stirring process.

[0056] Preferably, in step 1, after solid-liquid separation, the solid particles obtained are washed 2 to 4 times with methanol; more preferably, the washing method is centrifugal washing, the centrifugal speed is 6000 to 8000 r / min, and the centrifugation is 10 to 20 min.

[0057] Preferably, in step 2, after the solid particles and PEI (polyethyleneimine) are dispersed in the second solvent, the concentration of the solid particles in the second solvent is 10-30 g / L; the concentration of PEI in the second solvent is 10-30 g / L.

[0058] Preferably, in step 2, the second solvent is any one or both of DMF (N,N-dimethylformamide) and ethanol.

[0059] Preferably, in step 2, the oil bath temperature is 70-100° C., and the oil bath time is 15-30 h.

[0060] Preferably, in step 3, the concentration of precipitated particles in the spinning solution is 30-75 g / L; the concentration of PES in the spinning solution is 200-500 g / L.

[0061] If there is too much PES, the oxide content is too low and the mechanical properties of the membrane are reduced; if there is too little PES, the oxide content is too high and the spinning needle is easily blocked.

[0062] Preferably, in step 4, the polymer is any one or more of polytetrafluoroethylene, nitrile rubber, polyethylene oxide, and silicone rubber.

[0063] Preferably, in step 4, the third solvent is any one or more of toluene, chloroform, anisole and xylene.

[0064] Preferably, in step 4, the concentration of the active substance in the slurry is 100-400 g / L; the concentration of the polymer in the slurry is 4-16 g / L.

[0065] If there is an excess of polymer, the inorganic nanofiber membrane obtained by weaving will be too thick, resulting in increased resistance; if there is too little active substance, the inorganic nanofiber membrane obtained by weaving will be too thin, and the assembled battery will be prone to short circuit.

[0066] Preferably, 0.12-0.2 g of slurry is dripped onto each square centimeter of the inorganic nanofiber membrane.

[0067] In a third aspect, the present invention provides a battery comprising the above-mentioned solid electrolyte membrane or the solid electrolyte membrane prepared by the above-mentioned preparation method.

[0068] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0069] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0070] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0071] Embodiment 1:

[0072] A method for preparing a solid electrolyte membrane comprises the following steps:

[0073] Step 1, add 3g Al2O3 nanoparticles and GPTMS into 150mL toluene, the concentration of GPTMS in toluene is 0.2mol / L, heat the mixture of Al2O3, GPTMS and toluene in an oil bath at 100℃ for 12h, stir the mixture with a constant temperature magnetic stirrer, then separate the solid and liquid, add the separated solid particles into 150mL ethanol and centrifuge at 8000r / min for 15min, then separate the solid and liquid, repeat the ethanol washing three times, and the final solid particles are GPTMS-modified Al2O3, recorded as G-Al2O3.

[0074] Step 2, 2g of G-Al2O3 was ultrasonically dispersed in 150mL of DMF, 2g of PEI was added to the mixture and the pH value was adjusted to 8, and then the mixture was placed in an oil bath at 80°C and magnetically stirred for 18h. The obtained precipitate was Al2O3 nanoparticles modified with PEI and GPTMS, which was recorded as A-Al2O3.

[0075] Step 3, take 0.12g of A-Al2O3 obtained in step 2 and 0.8g of PES powder, add them to 2mL DMF and stir for 5h to obtain a spinning solution. The spinning solution is evenly divided into two pipettes with a needle inner diameter of 0.8mm and installed on an electrospinning machine. Under the conditions of high voltage 30kV, material connection distance 15cm, and extrusion speed 0.1mL / h, the spinning solution is drawn into filaments and connected by a material connection roller with a diameter of 8cm and a speed of 10r / min. When the thickness of the spinning membrane reaches 30μm, stop spinning, and the obtained membrane is an A-Al2O3-SPE inorganic nanofiber membrane.

[0076] Step 4: Mix 2 g of Li6PS5Cl with 0.08 g of polytetrafluoroethylene powder and 8 mL of toluene to form a slurry.

[0077] Step 5, place the A-Al2O3-SPE inorganic nanofiber membrane on a glass plate, take 4g of the slurry prepared in step 4 and drop it on the A-Al2O3-SPE inorganic nanofiber membrane with an area of ​​5×5cm, and then transfer the A-Al2O3-SPE inorganic nanofiber membrane to a glove box with an argon atmosphere for drying. After the toluene evaporates, the A-Al2O3-SPE inorganic nanofiber membrane is transferred to an oven and dried at 80°C for 8h under a vacuum atmosphere to obtain a solid electrolyte membrane.

[0078] Figure 1 This is the SEM image of the A-Al2O3-SPE inorganic nanofiber membrane prepared in step 3 of Example 1. Figure 1 It can be observed that the oxides are uniformly dispersed on the surface of the inorganic nanofiber membrane.

[0079] Embodiment 2:

[0080] A method for preparing a solid electrolyte membrane comprises the following steps:

[0081] Step 1, add 2g SiO2 nanoparticles and GPTMS into 180mL toluene, the concentration of GPTMS in toluene is 0.13mol / L, heat the mixture of SiO2, GPTMS and toluene in an oil bath at 110°C for 10h, stir the mixture with a constant temperature magnetic stirrer, then separate the solid and liquid, add the separated solid particles into 180mL ethanol and centrifuge at 8000r / min for 15min; then wash with ethanol three times and centrifuge to obtain solid particles, the solid particles are GPTMS-modified SiO2, recorded as G-SiO2.

[0082] Step 2: 1.8 g of G-SiO2 was ultrasonically dispersed in 100 mL of DMF, 3 g of PEI was added to the mixture and the pH value was adjusted to 9, and then the mixture was placed in an oil bath at 80°C and magnetically stirred for 15 h. The resulting precipitate was SiO2 nanoparticles modified with PEI and GPTMS, which was recorded as A-SiO2.

[0083] Step 3, take 0.1g of A-SiO2 obtained in step 2 and 0.6g of PES powder and add them to 2mL DMF and stir for 4h to obtain a spinning solution. The spinning solution is evenly divided into two pipettes with a needle inner diameter of 0.8mm and installed on an electrospinning machine. Under the conditions of high voltage 20kV, material connection distance 18cm, and extrusion speed 0.12mL / h, the spinning solution is drawn into filaments and connected by a material connection roller with a diameter of 9cm and a speed of 11r / min. When the thickness of the spinning membrane reaches 35μm, spinning is stopped, and the obtained membrane is an A-SiO2-SPE inorganic nanofiber membrane.

[0084] Step 4, mix 1gLi 10 GP2S 12 The mixture was mixed with 0.03 g of polyethylene oxide powder and 5 mL of anisole to form a slurry.

[0085] Step 5, placing the A-SiO2-SPE inorganic nanofiber membrane on a glass plate, taking 3g of the slurry prepared in step 4 and dropping it on the A-SiO2-SPE inorganic nanofiber membrane with an area of ​​5×5cm, and then transferring the A-SiO2-SPE inorganic nanofiber membrane to a glove box with an argon atmosphere for drying. After the toluene evaporates, the A-SiO2-SPE inorganic nanofiber membrane is transferred to an oven and dried at 60°C under a vacuum atmosphere for 5h to obtain a solid electrolyte membrane.

[0086] Figure 2 This is the SEM image of the A-SiO2-SPE inorganic nanofiber membrane prepared in step 3 of Example 2. Figure 2 It can be observed that the oxides are uniformly dispersed on the surface of the inorganic nanofiber membrane.

[0087] Embodiment 3:

[0088] A method for preparing a solid electrolyte membrane comprises the following steps:

[0089] Step 1, add 5g MgO nanoparticles and 1GPTMS into 200mL toluene, the concentration of GPTMS in toluene is 0.27mol / L, heat the mixture of MgO, GPTMS and toluene in an oil bath at 95°C for 10h, stir the mixture with a constant temperature magnetic stirrer, then separate the solid and liquid, add 200mL ethanol to the separated solid particles and centrifuge at 7000r / min for 15min; then wash with ethanol three times and centrifuge to obtain solid particles, the solid particles are GPTMS-modified Al2O3, recorded as G-MgO.

[0090] Step 2, 3g of G-MgO was ultrasonically dispersed in 100mL of DMF, 3g of PEI was added to the mixture, and the pH value was adjusted to 8.5, and then the mixture was placed in an oil bath at 85°C and magnetically stirred for 30 hours. The resulting precipitate was MgO2 nanoparticles modified with PEI and GPTMS, and was recorded as A-MgO.

[0091] Step 3, take 0.1g of A-MgO obtained in step 2 and 1g of PES powder, add them to 3mL DMF and stir for 6h to obtain a spinning solution. The spinning solution is evenly divided into two pipettes with a needle inner diameter of 0.8mm and installed on an electrospinning machine. Under the conditions of high voltage 25kV, a material connection distance of 20cm, and an extrusion speed of 0.15mL / h, the spinning solution is drawn into filaments and connected by a material connection roller with a diameter of 10cm and a speed of 12r / min. When the thickness of the spinning membrane reaches 40μm, spinning is stopped, and the obtained membrane is an A-MgO-SPE inorganic nanofiber membrane.

[0092] Step 4, mix 2gLi 5.7 PS 4.7 Cl 1.3 It was mixed with 0.08 g of nitrile rubber powder and 8 mL of xylene to form a slurry.

[0093] Step 5, placing the A-MgO-SPE inorganic nanofiber membrane on a glass plate, taking 5 g of the slurry prepared in step 4 and dropping it on the A-MgO-SPE inorganic nanofiber membrane with an area of ​​5×5 cm, and then transferring the A-MgO-SPE inorganic nanofiber membrane to a glove box with an argon atmosphere for drying. After the toluene evaporates, the A-MgO-SPE inorganic nanofiber membrane is transferred to an oven and dried at 80° C. for 8 h under a vacuum atmosphere to obtain a solid electrolyte membrane.

[0094] Figure 3 This is the SEM image of the A-MgO-SPE inorganic nanofiber membrane prepared in step 3 of Example 3. Figure 3It can be observed that the oxides are uniformly dispersed on the surface of the inorganic nanofiber membrane.

[0095] Comparative Example 1:

[0096] A method for preparing a solid electrolyte membrane comprises the following steps:

[0097] Step 1: 3 g of Al2O3 nanoparticles and GPTMS were added to 150 mL of toluene, the concentration of GPTMS in toluene was 0.2 mol / L, the mixture of Al2O3, GPTMS and toluene was heated in an oil bath at 100°C for 12 h, and the mixture was stirred by a constant temperature magnetic stirrer, followed by solid-liquid separation, the separated solid particles were added to 150 mL of ethanol and centrifuged at 8000 r / min for 15 min, followed by solid-liquid separation, and the ethanol washing was repeated three times. The solid particles finally obtained were GPTMS-modified Al2O3, denoted as G-Al2O 32 .

[0098] Step 2, take 0.12g of G-Al2O3 obtained in step 1 and 0.8g of PES powder and add them to 2mL DMF and stir for 5h to obtain a spinning solution. The spinning solution is evenly divided into two pipettes with a needle inner diameter of 0.8mm and installed on an electrospinning machine. Under the conditions of high voltage 30kV, material connection distance 15cm, and extrusion speed 0.1mL / h, the spinning solution is drawn into filaments and connected by a material connection roller with a diameter of 8cm and a speed of 10r / min. When the thickness of the spinning membrane reaches 30μm, stop spinning, and the obtained membrane is a G-Al2O3-SPE inorganic nanofiber membrane.

[0099] Step 3: Mix 2 g of Li6PS5Cl with 0.08 g of polytetrafluoroethylene powder and 8 mL of toluene to form a slurry.

[0100] Step 4, placing the G-Al2O3-SPE inorganic nanofiber membrane on a glass plate, taking 4g of the slurry prepared in step 4 and dropping it on the A-Al2O3-SPE inorganic nanofiber membrane with an area of ​​5×5cm, and then transferring the G-Al2O3-SPE inorganic nanofiber membrane to a glove box with an argon atmosphere for drying. After the toluene evaporates, the G-Al2O3-SPE inorganic nanofiber membrane is transferred to an oven and dried at 80°C for 8h under a vacuum atmosphere to obtain a solid electrolyte membrane.

[0101] Comparative Example 2:

[0102] A method for preparing a solid electrolyte membrane comprises the following steps:

[0103] Step 1: 3 g of Al2O3 nanoparticles were ultrasonically dispersed in 150 mL of DMF, 2 g of PEI was added to the mixture, the pH value was adjusted to 8, and then heated in an oil bath at 80°C and magnetically stirred for 18 h. The resulting precipitate was PEI-modified Al2O3 nanoparticles, denoted as P-Al2O3.

[0104] Step 2, take 0.12g of P-Al2O3 obtained in step 1 and 0.8g of PES powder, add them to 2mL DMF and stir for 5h to obtain spinning solution. The spinning solution is evenly divided into two pipettes with a needle inner diameter of 0.8mm and installed on an electrospinning machine. Under the conditions of high voltage 30kV, material connection distance 15cm, and extrusion speed 0.1mL / h, the spinning solution is drawn into filaments and connected by a material connection roller with a diameter of 8cm and a speed of 10r / min. When the thickness of the spinning membrane reaches 30μm, stop spinning, and the obtained membrane is the P-Al2O3-SPE inorganic nanofiber membrane.

[0105] Step 3: Mix 2 g of Li6PS5Cl with 0.08 g of polytetrafluoroethylene powder and 8 mL of toluene to form a slurry.

[0106] Step 4, place the P-Al2O3-SPE inorganic nanofiber membrane on a glass plate, take 4g of the slurry prepared in step 4 and drop it on the P-Al2O3-SPE inorganic nanofiber membrane with an area of ​​5×5cm, and then transfer the P-Al2O3-SPE inorganic nanofiber membrane to a glove box with an argon atmosphere for drying. After the toluene evaporates, the P-Al2O3-SPE inorganic nanofiber membrane is transferred to an oven and dried at 80°C for 8h under a vacuum atmosphere to obtain a solid electrolyte membrane.

[0107] Comparative Example 3:

[0108] The difference from Example 1 is that in step 3, the PES composite A-Al2O3 fiber membrane is not used.

[0109] Comparative Example 4:

[0110] A method for preparing a solid electrolyte membrane comprises the following steps:

[0111] Step 1, take 0.12gAl2O3 and 0.8gPES powder and add them to 2mL DMF and stir for 5h to obtain spinning solution. The spinning solution is evenly divided into two pipettes with a needle inner diameter of 0.8mm and installed on the electrospinning machine. Under the conditions of high voltage 30kV, material connection distance 15cm, and extrusion speed 0.1mL / h, the spinning solution is drawn into filaments and connected by a material connection roller with a diameter of 8cm and a speed of 10r / min. When the thickness of the spinning membrane reaches 30μm, spinning is stopped, and the obtained membrane is the Al2O3-SPE inorganic nanofiber membrane.

[0112] Step 2: Mix 2 g of Li6PS5Cl with 0.08 g of polytetrafluoroethylene powder and 8 mL of toluene to form a slurry.

[0113] Step 3, place the Al2O3-SPE inorganic nanofiber membrane on a glass plate, take 4g of the slurry prepared in step 4 and drop it on the Al2O3-SPE inorganic nanofiber membrane with an area of ​​5×5cm, and then transfer the Al2O3-SPE inorganic nanofiber membrane to a glove box with an argon atmosphere for drying. After the toluene evaporates, transfer the Al2O3-SPE inorganic nanofiber membrane to an oven and dry it at 80°C under a vacuum atmosphere for 8h to obtain a solid electrolyte membrane.

[0114] The solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were assembled into batteries in the following manner:

[0115] The prepared composite electrolyte material is used as a solid electrolyte membrane, the nickel-cobalt-manganese 622 active material is used to prepare the positive electrode sheet, and the lithium-indium alloy sheet is used as the negative electrode sheet; the solid electrolyte membrane, the positive electrode sheet, and the negative electrode sheet are cut into discs with diameters of 18 mm, 16 mm, and 16 mm respectively by a slicer to assemble a sandwich-structured button-type solid-state battery.

[0116] The cycle performance of the battery was tested in the following way: the assembled button cell was tested at a rate of 0.3C using a battery charge and discharge tester (model CT3002A) from Wuhan Blue Electric Company, the test temperature was 25°C, and the voltage range was 2.8~4.3V.

[0117] Figure 4 The cycle performance test diagram of the battery assembled with the solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 is shown in FIG. Figure 4 It can be seen that Example 1, Example 2 and Example 3 all show good capacity retention rates, and Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 all have a large degree of attenuation, which can prove that the solid electrolyte membrane provided by the present invention can effectively improve the initial capacity and capacity retention rate of the battery, so that the battery can maintain a stable cycle for a long time.

[0118] The solid electrolyte membranes and lithium sheets prepared in Example 1 and Comparative Examples 1 to 4 were made into Li-Li symmetrical batteries. The battery had a current of 0.25 mA / cm 2 The current density was 25°C and the plating / stripping cycle was carried out. Each cycle lasted for 3 hours to evaluate the cycle stability of the composite solid electrolyte membrane and the lithium metal electrode. Figures 5 to 9It can be seen that the overpotential of the solid electrolyte membrane in Example 1 is low during the cycle, while the overpotentials of Comparative Examples 1 to 4 are relatively high compared to Example 1. The voltage of Comparative Examples 1 and 2 increases significantly as the cycle progresses, indicating that the internal resistance of the electrolyte increases, which is not conducive to the charge transfer of the battery and the transmission of lithium ions. Comparative Examples 3 and 4 experienced micro-short circuits caused by lithium dendrite puncture after 340h and 450h, respectively. Therefore, surface modification of the oxide in the inorganic nanofiber membrane has a positive effect on improving its electrochemical properties, so that the solid electrolyte has more excellent ionic conductivity and mechanical strength, further delays the formation of lithium dendrites, and improves the cycle stability of the battery.

[0119] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a solid electrolyte membrane, characterized in that: The steps include: Step 1, dispersing GPTMS and inorganic oxide in a first solvent, reacting in an oil bath, and performing solid-liquid separation to obtain solid particles; Step 2, dispersing the solid particles and PEI in a second solvent, adjusting the pH value of the reaction system to 8-9, and performing solid-liquid separation after oil bath reaction to obtain precipitated particles; Step 3, dispersing the precipitated particles and PES in a second solvent to obtain a spinning solution, drawing the spinning solution into filaments by electrospinning, and then preparing a modified inorganic nanofiber membrane; Step 4, dispersing the active material and the polymer in a third solvent to obtain a slurry, dropping the slurry on the modified inorganic nanofiber membrane, and drying under an inert atmosphere to obtain the solid electrolyte membrane; In step 4, the active materials are Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the above.

2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step 1, after GPTMS and inorganic oxide are dispersed in the first solvent, the concentration of inorganic oxide in the first solvent is 10~35g / L; the concentration of GPTMS in the first solvent is 0.13~0.27mol / L; the first solvent is any one or more of toluene, acetone, and ether; the oil bath temperature is 90~120℃, and the oil bath time is 10~15h.

3. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step 2, after the solid particles and PEI are dispersed in the second solvent, the concentration of the solid particles in the second solvent is 10-30 g / L; the concentration of PEI in the second solvent is 10-30 g / L; the oil bath temperature is 70-100° C., and the oil bath time is 15-30 h; the second solvent is any one or both of DMF (N,N-dimethylformamide) and ethanol.

4. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step 3, the concentration of precipitated particles in the spinning solution is 30-75 g / L; the concentration of PES in the spinning solution is 200-500 g / L.

5. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: In step 1, the inorganic oxide is any one or more of aluminum oxide, silicon oxide, and magnesium oxide; the polymer is any one or more of polytetrafluoroethylene, nitrile rubber, polyethylene oxide, and silicone rubber; and the third solvent is any one or more of toluene, chloroform, anisole, and xylene.

6. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The concentration of active substances in the slurry is 100-400 g / L; the concentration of polymers in the slurry is 4-16 g / L, and 0.12-0.2 g of slurry is dropped on each square centimeter of the inorganic nanofiber membrane.

7. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane is prepared by the preparation method of any one of claims 1 to 6; the solid electrolyte membrane comprises a modified inorganic nanofiber membrane and an active material, and the active material is coated on at least a portion of the surface of the modified inorganic nanofiber membrane; the modified inorganic nanofiber membrane is prepared by inorganic oxides modified by GPTMS (3-glycidyloxypropyltrimethoxysilane), PEI (polyethyleneimine) and PES (polyethersulfone).

8. A battery, characterized in that: A solid electrolyte membrane obtained by the method for preparing a solid electrolyte membrane according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lithium ion battery separation membrane and preparation method thereof, and lithium ion battery

    CN107799696A

  • Hybrid solid electrolyte for secondary battery and manufacturing method therefor

    CN109792077A